Peningkatan Efisiensi Kompor LPG Dengan Menggunakan Reflektor Radiasi Panas Bersirip - Sudarno, Sudarno; Fadelan, Fadelan (Semesta Teknika, 2015)
Heat wasted due to radiation from the flame around the LPG stovecan lower stove efficiency. The wasted heat would be exploited by using a finned heat reflector . The working principle of this tool is to capture the wasted heat and reflect to the load so that it becomes useful energy . Preliminary data indicate that areflector without fins can increase stove efficiency., The objective of this research isto determine the performace finned heat reflectorin increasing LPG stove efficiency. A piece of stainless steel plate as a truncated cone-shaped finned experimental model was used as a reflector. The efficiency test is done through boiling water test. The number of fin of the the same dimensions were varied, starting from one-line to three-line fins. The performance of the stoves using reflectorwith fins were compared with that of stove using reflector without finsand with that of stove without reflectot. Based on test results, it is found that the use of finned reflectors is able to increase the efficiency of LPG stoves. The highest efficiency is obtained on the use of reflectors with three rows of fins, which amounted to 44.09%. The magnitude of the increase is compared to without using a reflector at 5.22%, while compared with the reflector without fins for 5.01%. Based on the test of temperature distribution is obtained also that the use of reflector finned heat radiation can increase the area of complete combustion.